Caracterización hidrológica y socieconómica en la quebrada Jatuchimbana, ubicada en el páramo del Igualata, provincia de Tungurahua - López Macias, Jackeline Julady (2025)
This study focused on the water and socioeconomic characterization of the Jatuchimbana stream, located in the Igualata páramo, Tungurahua province. The study sought to evaluate the effectiveness of the conservation processes implemented in the area using environmental and socioeconomic indicators. In addition, a socioeconomic characterization of the area of interest was conducted. According to the ICA-NSF index, the water quality results within the study area in the stream were obtained from sampling points PM1, PM2, PM3, and PM4. The determined water quality values range from 57.4% to 61.74%, with a "Medium" quality. This is because agricultural and livestock activities that increase turbidity, TDS, nitrates, and phosphates are the main activities around the monitoring points, facing multiple challenges related to the conservation and sustainable use of water resources. The socioeconomic characterization conducted through surveys of 50 residents of the Guangalo community showed that the average cost of water per cubic meter is $2.25, and the average participation rate is seven milongas per year. In addition, a SWOT analysis was conducted to identify priorities and guide conservation and management actions for the Jatuchimbana stream. The conclusions highlight the need to implement GAP (good agricultural practices) to minimize the contribution of pollutants to the water system. Furthermore, the local community needs to be raised aware of the importance of conserving and protecting water resources and promoting proper waste management to mitigate pollution. Sustainable management strategies, such as reforestation with native species and constant monitoring of land-use changes, are used to ensure wáter sustainability.